STRATEGI KEANDALAN PELAYANAN PADA PT. BPRS SARANA PRIMA MANDIRI - Subaida Subaida; Mansur Mansur; Ridan Muhtadi (Faculty of Islamic Economics and Business, 2020)
Introduction: The purpose of this study was to determine the service reliability strategy in serving customers. This service strategy is a supporting factor for the marketing activities of all products in order to achieve customer satisfaction. Methods: The research methodology used is a qualitative descriptive. Data collection techniques using observation documentation interviews. Results: The results of this study indicate that the reliability of this service is quite good and in accordance with its field. However, the SPM Pamekasan Bank does not have an ATM. In overcoming these shortcomings SPM banks by improving service quality by using service reliability. So that customers feel satisfied and even become loyal customers. So in this case the SPM Pamekasan Bank is one of the services that is in accordance with the expectations of the community. Keywords: Service reliability strategy, Customer satisfaction